Pengaruh Peran Atribut Destinasi Mice Terhadap Minat Kunjungan Wisatawan Di Kota Solo yang Dimediasi Service Quality - Sudarsi; Yuliyani (STIE Pariwisata API Yogyakarta, 2025)
The purpose of this study was to determine the influence of the role of MICE destination attributes on tourist visit interest in the city of Solo mediated by Service Quality. This research method used quantitative research. This study used a purposive sampling data collection technique with data analysis using the Smart PLS test. The results of this study prove that the accessibility variable influences service quality. The attraction variable influences service quality. The accessibility variable influences visit interest. The attraction variable influences visit interest. The service quality variable influences visit interest. The service quality variable can provide an illustration that service quality can be a mediating variable between the accessibility and attraction variables on the visit interest variable